Development of a cavity with photonic crystal structure for axion searches. (30th April 2021) - Kishimoto, Y; Suzuki, Y; Ogawa, I; Mori, Y; Yamashita, M
Abstract: Two cavities of different sizes with a photonic crystal structure have been developed for axion searches. In the cavities, the dispersion relation in the photonic crystal is utilized, and so they are called "DRiPC cavities". The size of the smaller cavity is 100 × 100 × 10 mm, where 16 cylindrical metal poles with a diameter of 4 mm are introduced in a 4×4 grid at 20 mm intervals. In this study, the grid interval in the x direction in the smaller cavity, L_x, was changed to investigate the resonance frequency, Q -value, and the electric field profile at each L_x . The lowest three frequencies have been compared with those simulated by the finite element method and have been found to be in excellent agreement. The lowest-frequency mode could be tuned from 5.10 GHz (L_x = 25.0 mm) to 6.72 GHz (13.9 mm), centered on 5.87 GHz at L_x = 20 mm. This wide tunability range, 27.7%, was suitable for a search with a modest Q -value. By examining the electric field distributions with the bead-pull method, the lowest-frequency modes at L_x=16.0 –25.0 mm were TM_010 -like. This mode was also obtained in a larger cavity (180 × 180 × 20 mm × 2 ) with the same photonic crystal structure. These results led us to conclude that a DRiPC cavity has features suitable for future axion search experiments.